C♯ for programmers - Deitel, Harvey M., 1945- (Deitel developer series., 2005)
A new edition of this title is available, ISBN-10: 0137144156 ISBN-13: 9780137144150 The practicing programmer's DEITEL® guide to C# and the powerful Microsoft .NET Framework Written for programmers with a background in C++, Java, or other high-level languages, this book applies the Deitel signature live-code approach to teaching programming and explores Microsoft's C# language and the new .NET 2.0 in depth. The book is updated for Visual Studio® 2005 and C# 2.0, and presents C# concepts in the context of fully tested programs, complete with syntax shading, detailed line-by-line code descriptions, and program outputs. The book features 200+ C# applications with 16,000+ lines of proven C# code, as well as 300+ programming tips that will help you build robust applications. Start with a concise introduction to C# fundamentals using an early classes and objects approach, then rapidly move on to more advanced topics, including multithreading, XML, ADO.NET 2.0, ASP.NET 2.0, Web services, network programming, and .NET remoting. Along the way you will enjoy the Deitels' classic treatment of object-oriented programming and a new, OOD/UML"!ATM case study, including a complete C# implementation. When you are finished, you will have everything you need to build next-generation Windows applications, Web applications, and Web services. Dr. Harvey M. Deitel and Paul J. Deitel are the founders of Deitel and Associates, Incorporated, the internationally recognized programming languages content-creation and corporate-training organization. Together with their colleagues at Deitel and Associates, Incorporated, they have written many international best-selling programming languages textbooks that millions of people worldwide have used to master C, C++, Java"! C#, XML, Visual Basic®, Perl, Python, and Internet and Web programming. The DEITEL® Developer Series is designed for practicing programmers. The series presents focused treatments of emerging technologies, including .NET, J2EE, Web services, and more. Pre-publication Reviewer Testimonials "Excellent coverage of developing ASP.NET 2.0 applications, with plenty of sample code. The chapter on exception handling is one of, if not the best such chapters I have seen in the 50+ .NET related books I've read and reviewed. The chapter on Networking is one of the best I have seen."--Peter Bromberg, Merrill Lynch, C# MVP "A comprehensive introduction to XML, and one of the clearest tutorials on Web services I've read, with great examples ...